sendmail Cookbook - Hunt, Craig (O'Reilly, 2011)
The sendmail Cookbook provides step-by-step solutions for the administrator who needs to solve configuration problems fast. Each recipe in the sendmail Cookbook outlines a configuration problem, presents the configuration code that solves that problem, and then explains the code in detail. The book also provides lots of new material that doesn't get much coverage elsewhere--STARTTLS and AUTH are given entire chapters, and LDAP is covered in recipes throughout the book.